PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PEMBELAJARAN PAI DI MAN 1 SUNGAI PENUH - Masnur Alam (Tarbawi : Jurnal Ilmu Pendidikan, 2018)
The aims of this research are to describe: (1) the advantages of Contextual Teaching and Learning (CTL) learning models; (2) Environmental material and efforts to preserve it; (3) Application of Contextual Teaching and Learning learning models in Islamic Education. This research is a field research study, with qualitative methods. The main instruments are observation, in-depth interview, and documentation. Research findings are: (1) The Contextual Teaching and Learning learning model can increase activity, creativity, independence to find material that is learned, as well as being able to explore, discuss, understand, and apply in daily life. (2) Environmental material consisting of biotic and nonbiotic which is very beneficial for living things, the effort to preserve it is by replanting, not exploiting, cutting, burning, penetrating, use must be in accordance with environmental ethics. (3) The application of the CTL model is in accordance with the existing steps, and has succeeded in activating students to seek, understand their own environmental theories, and be motivated to actualize in everyday life and be able to correlate with real life. The Islamic Educational teacher has been able to demonstrate one of the CTL principles namely making himself a model, role model, uswatun hasanah or a good example of preserving the environment.